A network meta‐analysis of threats to South American fish biodiversity. Issue 4 (15th April 2019) - Bezerra, Luis Artur Valões; Freitas, Matheus Oliveira; Daga, Vanessa Salete; Occhi, Thiago Vinicius Trento; Faria, Larissa; Costa, Ana Paula Lula; Padial, Andre Andrian; Prodocimo, Viviane; Vitule, Jean Ricardo Simões
Abstract: While environmental alterations have made Homo sapiens the hyperkeystone species of the globe, biotic homogenization initiated a new era, the "Homogenocene." Still, some terrestrial and aquatic ecosystems in South America are considered pristine and wild, which can lead to a general faith that economic progress is consistent with conservation strategies, even without scientific support. We compiled anthropogenic threats to fish biodiversity in a hierarchical meta‐analysis, along with an evidence synthesis of threats related to biological invasions, based on peer‐reviewed research with the aim to represent the actual conservation status of the South American ichthyofauna. We highlighted human‐related threats and synergistic effects of biological invasions, climate change, environmental alterations (e.g., pollution, aquaculture and damming) and fisheries. Considering measures that reinforce novel alien fish (e.g., artificial hybrids or genetically modified) introductions, it became clear why an eventual increase in local or regional species richness is not always beneficial to aquaculture, biodiversity, human well‐being or nature. In fact, citizens in all societal roles, including scientists, should revise their concepts about threats to fish biodiversity. Environmental policies require more than taxonomic diagnostics to achieve conservation goals under an incompatible scenario of a multiplying number of fish species and biotic homogenization. We advocate for countries in South America using science‐based strategies useful to maintain their social and economic growth along with their "remaining nature." We live a crucial moment when the government overlooks threats to biodiversity and uses agribusiness as the most acceptable manner of fuelling the economy.